Cloning of a cDNA for steroid sulfatase: frequent occurrence of gene deletions in patients with recessive X chromosome-linked ichthyosis. - Bonifas, J M (1987)
A human steroid sulfatase (steryl-sulfatase; steryl-sulfate sulfohydrolase, EC 3.1.6.2) cDNA 2.4 kilobases long was isolated from a human placental lambda gt11 cDNA expression library. The library was screened with monospecific rabbit antibodies elicited by injection of steroid sulfatase protein purified from human placentas. Hybridization of the cDNA with EcoRI-digested genomic DNA indicated that patients from 14 of 15 apparently unrelated families have gross deletions of the gene for steroid sulfatase. One patient had genomic DNA fragments that were identical to those from normal individuals, indicating the absence of any major deletions as the cause of his lack of steroid sulfatase enzyme activity.